Oral and depot progestin therapy for endometriosis: towards a personalized medicine. (13th October 2017) - Buggio, Laura; Somigliana, Edgardo; Barbara, Giussy; Frattaruolo, Maria Pina; Vercellini, Paolo
ABSTRACT: Introduction : Endometriosis is an estrogen-dependent chronic inflammatory disorder that requires a life-long management plan. Long-term adherence to treatment is pivotal to ensure an effective clinical management. In this optic, one of the cornerstone of endometriosis medical treatment is represented by progestins. Areas covered : This narrative review examines the clinical efficacy, safety and tolerability of oral and depot progestins used in the treatment of endometriosis. The material included in the current manuscript was obtained with a MEDLINE search through PubMed from inception until February 2017. Expert opinion : Progestins are effective in controlling pain symptoms in the majority of women with endometriosis, and their effect seems not inferior to that achieved with other compounds used to treat the disease, such as gonadotropin-releasing hormone agonist. Available progestins include a broad range of both oral and depot compounds, and represent, in most cases, an inexpensive treatment option. In addition, progestins do not increase significantly thrombotic risk and could be adopted in those women with metabolic or cardiovascular contraindication to estrogen-progestins. The choice between the different available compounds should be tailored for every woman with preference to the most cost-effective treatment, depending on the most complained symptom and disease location.